2005
DOI: 10.1101/gr.3274805
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of long-lived C. elegans daf-2 mutants using serial analysis of gene expression

Abstract: We have identified longevity-associated genes in a long-lived Caenorhabditis elegans daf-2 (insulin/IGF receptor) mutant using serial analysis of gene expression (SAGE), a method that efficiently quantifies large numbers of mRNA transcripts by sequencing short tags. Reduction of daf-2 signaling in these mutant worms leads to a doubling in mean lifespan. We prepared C. elegans SAGE libraries from 1, 6, and 10-d-old adult daf-2 and from 1 and 6-d-old control adults. Differences in gene expression between daf-2 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
174
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(195 citation statements)
references
References 61 publications
14
174
0
2
Order By: Relevance
“…A general decrease in metabolic activity for daf-2 adults was detected in a previous study (Halaschek-Wiener et al, 2005;McElwee et al, 2006), and here we describe the affected pathways, in common between daf-2 adults and dauer larvae. There is an indication that transcripts for enzymes of the TCA cycle are lowered in both types of long-lived worms, although mechanisms that might compensate for reduced TCA cycle activity appear to involve different pathways, fermentation in dauer larvae versus the glyoxylate shunt in daf-2 adults.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A general decrease in metabolic activity for daf-2 adults was detected in a previous study (Halaschek-Wiener et al, 2005;McElwee et al, 2006), and here we describe the affected pathways, in common between daf-2 adults and dauer larvae. There is an indication that transcripts for enzymes of the TCA cycle are lowered in both types of long-lived worms, although mechanisms that might compensate for reduced TCA cycle activity appear to involve different pathways, fermentation in dauer larvae versus the glyoxylate shunt in daf-2 adults.…”
Section: Discussionsupporting
confidence: 75%
“…Whereas McElwee et al (2004) used cDNA microarrays for a similar comparison, we used Serial Analysis of Gene Expression, or SAGE (Velculescu et al, 1995) to identify potential novel regulators of life span, and to characterize the expression profiles of different gene families that were previously shown to be associated with aging (Lund et al, 2002;Murphy et al, 2003). SAGE data for daf-2 and wild-type adults were compared in a previous study (Halaschek-Wiener et al, 2005), which showed general inhibition of metabolism in the middleaged daf-2 adults.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the transcriptional profiles of the dauer stage with that of long-lived daf-2 showed that many DAF-16-dependent genes are common in both transcriptional outputs (22). Hierarchical clustering of genes with altered expression during aging in wild-type N2 and long-lived daf-2 identified one functional group of genes that is common to both strains as well as one that is specific for the N2 strain (20,22,23). Heat shock genes are induced until mid-age and then reduced in later life in both strains.…”
Section: Global Gene Expression Of Aging In C Elegansmentioning
confidence: 99%
“…This is also consistent with several daf-2 microarray and serial analysis of gene expression (SAGE) experiments. [22][23][24] DAF-28/Insulin and DAF-2/IR negatively regulate DAF-18/PTEN in neurons and intestine To gain insight into what tissues the DAF-28/Insulin and DAF-2/IR negatively regulate DAF-18/PTEN, we performed an in situ antibody staining on these mutants. Consistent with our immunoblots, we found that wild-type animals have low levels of DAF-18/ PTEN and is not detected in neurons or intestinal cells.…”
Section: Introductionmentioning
confidence: 99%